Expanding our knowledge of Synurales (Chrysophyceae) in Florida, United States: Proposing three novel Mallomonas taxa - Knotek, Petr; Pusztai, Martin; Jadrná, Iva; Škaloud, Pavel (Journal of phycology, 2025)
We conducted a survey of Synurales diversity in Florida (United States), focusing on two established hotspots-Ocala National Forest and Myakka River State Park-and two previously unexplored sites-Manatee Lake and Lake Lee. Using transmission electron microscopy (TEM), we identified 69 species, increasing the total number recorded from Florida to 90. Among these, three species-Mallomonas cornea sp. nov., M. laureana sp. nov., and M. joergenii sp. nov.-have been newly described based on detailed morphological and molecular analyses. We have also proposed a new combination, M. poseidonii comb. et stat. nov., and established a new section, Corneae sect. nov., based on molecular phylogenetics. Our findings revealed an independent emergence of ribbed scale shield ornamentation in M. joergenii sp. nov. and suggested that internal scale reticulation in M. laureana sp. nov. may be an adaptation to high UV irradiance in tropical environments. This study underscores the value of DNA sequence data in resolving taxonomic ambiguities, elucidating evolutionary patterns, and enhancing species recovery from type localities.
Keywords: Florida; electron microscopy; Synurales; siliceous scales; phylogeny; biodiversity hotspot; taxonomy; new species; adaptation